2018
DOI: 10.1103/physrevb.97.045132
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Kondo state in two-dimensional semiconducting phosphorene

Abstract: Correlated interaction between dilute localized impurity electrons with the itinerant host conduction electrons in metals gives rise to the conventional many-body Kondo effect below sufficiently low temperature. In sharp contrast to these conventional Kondo systems, we report an intrinsic, robust and high-temperature Kondo state in two-dimensional semiconducting phosphorene. While absorbed at a thermodynamically stable lattice defect, Cr impurity triggers an electronic phase transition in phosphorene to provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The effect of uniaxial strain on the electronic structure of SLP has been studied earlier within the conventional exchange-correlation functional. [20,63,65,66] However, the considerations of self-energy correction and electronhole interaction are scarce in this regard. Here, we investigate the QP and optical gaps; and the corresponding exciton binding for SLP under ε a/z s = ±5% uniaxial strain (Table I), while the strained lattice is relaxed along the transverse direction.…”
Section: B Effect Of Uniaxial Strainmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of uniaxial strain on the electronic structure of SLP has been studied earlier within the conventional exchange-correlation functional. [20,63,65,66] However, the considerations of self-energy correction and electronhole interaction are scarce in this regard. Here, we investigate the QP and optical gaps; and the corresponding exciton binding for SLP under ε a/z s = ±5% uniaxial strain (Table I), while the strained lattice is relaxed along the transverse direction.…”
Section: B Effect Of Uniaxial Strainmentioning
confidence: 99%
“…We earlier reported that the strain energy along the zigzag direction is much higher compared to the same along the armchair direction and thus, straining the SLP along the armchair direction is comparatively easier. [20] Within −5% ε a/z s +5% strain and optical E opt g gaps are calculated within the G2W0 and G2W0-BSE approaches, respectively, which are subsequently interpolated to Lz → ∞. The parameters for the simplified exciton model, the effective carrier masses m * e and m * h along the armchair and zigzag directions; and the average static dielectric constant are calculated within the HSE06 hybrid functional.…”
Section: B Effect Of Uniaxial Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…[7,[12][13][14] Further, many exotic quantum manybody states have been theoretically predicted and experimentally demonstrated in few-layer phosphorene. [15][16][17] However, the major hurdle is the inferior stability of phosphorene at ambient conditions compared to graphene and transition-metal dichalcogenides. The degradation in two-dimension results from the dynamics of lattice defects and chemical interaction with the environment.…”
Section: Introductionmentioning
confidence: 99%